Promoting Self-Efficacy of Nursing Students in Academic Integrity Through a Digital Serious Game: A Pre/Post-Test Study - Laura Creighton; Christine Brown Wilson; Tara Anderson; Conor Hamilton; Guy Curtis; Christine Slade; Gary Mitchell (Nursing Reports)
Background: Academic integrity is an important component of nursing education, bridging academic ethics with professional practice. This study evaluated the effectiveness of a co-designed Academic Integrity digital serious game in improving nursing students’ self-efficacy related to academic integrity, academic offenses, professionalism, and artificial intelligence use. Methods: A pre-test/post-test design was employed, using a bespoke questionnaire to assess 303 first-year nursing students’ self-efficacy before and after playing the game. The questionnaire covered five subscales: academic integrity standards, academic offenses, professional values, feedback processes, and AI use in academic work. Results: Statistically significant improvements were observed across all subscales following the intervention, indicating enhanced self-efficacy in understanding and applying academic integrity principles, recognizing academic offenses, demonstrating professional behaviors, utilizing feedback, and appropriately using AI in academic contexts. Conclusions: The Academic Integrity digital serious game has the potential to be an effective tool for enhancing nursing students’ self-efficacy in the areas of academic and professional ethics. This approach shows promise for integrating academic integrity-based education in nursing curricula and preparing students for the ethical challenges of modern healthcare practice. This study was not registered.